Radial nerve palsy. Issue 8 (9th August 2016) - Bumbasirevic, Marko; Palibrk, Tomislav; Lesic, Aleksandar; Atkinson, Henry DE
Abstract : As a result of its proximity to the humeral shaft, as well as its long and tortuous course, the radial nerve is the most frequently injured major nerve in the upper limb, with its close proximity to the bone making it vulnerable when fractures occur. Injury is most frequently sustained during humeral fracture and gunshot injuries, but iatrogenic injuries are not unusual following surgical treatment of various other pathologies. Treatment is usually non-operative, but surgery is sometimes necessary, using a variety of often imaginative procedures. Because radial nerve injuries are the least debilitating of the upper limb nerve injuries, results are usually satisfactory. Conservative treatment certainly has a role, and one of the most important aspects of this treatment is to maintain a full passive range of motion in all the affected joints. Surgical treatment is indicated in cases when nerve transection is obvious, as in open injuries or when there is no clinical improvement after a period of conservative treatment. Different techniques are used including direct suture or nerve grafting, vascularised nerve grafts, direct nerve transfer, tendon transfer, functional muscle transfer or the promising, newer treatment of biological therapy. Cite this article: Bumbasirevic M, Palibrk T, Lesic A, Atkinson HDE. Radial nerve palsy. EFORT Open Rev 2016;1:286-294. DOI: 10.1302/2058-5241.1.000028.